In situ generated cationic Pd(II)/bipyridine-catalyzed addition of arylboronic acids to N-sulfonyl-arylaldimines. Issue 21 (24th May 2017) - Yang, Zhenyu; Ni, Yuxin; Liu, Rui; Song, Kaixuan; Lin, Shaohui; Pan, Qinmin
Graphical abstract: Highlights: Highly reactive cationic Pd(II)-bpy was in situ generated in CH3 NO2 . High yielded Pd(II)-catalytic addition to arylaldimines was optimized. Air and moisture insensitive Pd(II)-catalysis was developed. 12 of 13 examples yielded >90% and showed high functional groups tolerance. Abstract: An in situ generated cationic Pd(II)/bipyridine-catalyzed nucleophilic addition of arylboronic acids to N -sulfonyl arylaldimines was developed and optimized, and the reaction was proceeded highly efficiently and conveniently in CH3 NO2 . A series of arylboronic acids and N -sulfonyl arylaldimines were surveyed, and 12 of 13 examples gave 90∼96% yields.